Adaptive mutation in influenza A virus non-structural gene is linked to host switching and induces a novel protein by alternative splicing - Selman, Mohammed; Dankar, Samar K; Forbes, Nicole E; Jia, Jian-Jun; Brown, Earl G (Université d'Ottawa | University of Ottawa, 2012)
Little is known about the processes that enable influenza A viruses to jump into new host species. Here we show that the non-structural protein1 nucleotide substitution, A374G, encoding the D125G(GATGGT) mutation, which evolved during the adaptation of a human virus within a mouse host, activates a novel donor splice site in the non-structural gene, hence producing a novel influenza A viral protein, NS3. Using synonymous 125G mutations that do not activate the novel donor splice site, NS3 was shown to provide replicative gain-of-function. The protein sequence of NS3 is similar to NS1 protein but with an internal deletion of a motif comprised of three antiparallel β-strands spanning codons 126 to 168 in NS1. The NS1-125G(GGT) codon was also found in 33 natural influenza A viruses that were strongly associated with switching from avian to mammalian hosts, including human, swine and canine populations. In addition to the experimental human to mouse switch, the NS1-125G(GGT) codon was selected on avian to human transmission of the 1997 H5N1 and 1999 H9N2 lineages, as well as the avian to swine jump of 1979 H1N1 Eurasian swine influenza viruses, linking the NS1 125G(GGT) codon with host adaptation and switching among multiple species.
Keywords: influenza A virus; non-structural protein 1; NS gene; NS3; NS1; viral splicing; host switch